IMPLEMENTASI PENANAMAN NILAI-NILAI KEAGAMAAN ANAK PADA TAMAN KANAK-KANAK SE-KECAMATAN SUKARAMI KOTA PALEMBANG - Nurhayati; Akmal Hawi; Ahmad Zainuri; Ari Sandi (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
Implementation of religious values ​​towards children in kindergarten includes three fields, namely the field of faith, the field of worship, and the field of morals. This study aims to analyze the role of the teacher and its implementation as well as the impact of instilling religious values ​​in children in kindergartens in the Sukarami District of Palembang. This research is a qualitative research method with a descriptive approach. The results showed that the inculcation of Islamic religious values ​​in kindergarten age children was carried out by the teacher by using the play method, the habituation method, the story method, the tour travel method, the exemplary method, the demonstration method, and the question and answer method, so that the teacher delivered the teachings of religion, Islam, to students can know about the existence of Allah SWT, know the existence of angels, know the existence of prophets and apostles, know how to do the prayer, know about the laudable morals and despicable morals, even though students have not been organized, are not focused and the practice of worship is still not clear.